Inverse Electron Demand Diels-Alder Reactions of Heterocyclic Azadienes: [4 + 2] Cycloaddition Reaction of Amidines with 1,3,5-Triazines - Boger, Dale L; Kochanny, Monica J (Journal of organic chemistry, 1994)
A detailed study of the scope of the amidine Diels-Alder reaction with 1,3,5-triazines is described. The thermal reaction of amidines with symmetrical 1,3,5-triazines proceeds with in situ amidine to 1,1-diaminoethene tautomerization, [4 + 2] cycloaddition with the 1,3,5-triazine, loss of ammonia from the initial Diels-Alder adduct with imine generation, imine to enamine tautomerization, and retro Diels-Alder loss of ethyl cyanoformate to provide substituted 4-aminopyrimidines in excellent conversions. The reaction proceeds best with the amidine hydrochloride salts at intermediate reaction temperatures (90-100 degrees C) in polar, aprotic solvents, is rather invariant to the ratio of dienophile-diene used (1:2 congruent to 1:1 congruent to 2:1), and is subject to triazine substitutent effects characteristic of an inverse electron demand Diels-Alder reaction (R = CO(2)Et > R = H >> R = SCH3). Notably, the generality of the amidine [4 + 2] cycloaddition reaction with 1,3,5-triazines which has been extended to include cyclic amidines effectively addresses the limitations of the alternative ynamine or N,O-ketene acetal dienophiles. A comparative examination of amidines, thioimidates, and imidates revealed that amidines are uniquely suited for use in this reaction cascade.